Recent advances in the treatment and delivery system of diabetic retinopathy - Wang, Zhiyi; Zhang, Ningzhi; Lin, Pei; Xing, Yiqiao; Yang, Ning (Frontiers in Endocrinology, 2024)
Diabetic retinopathy (DR) is a highly tissue-specific neurovascular complication of type 1 and type 2 diabetes mellitus and is among the leading causes of blindness worldwide. Pathophysiological changes in DR mainly include neurodegeneration, inflammation, and oxidative stress. For patients with DR, drugs such as anti- vascular endothelial growth factor, steroids, laser photocoagulation, and vitrectomy have been widely used. However, these treatments are not completely effective in preventing DR progressing to blindness, and they have some adverse reactions respectively. Therefore, there is an urgent need to develop novel treatment strategies. This review aimed to summarize the current pathophysiology, therapeutic approaches, and available drug-delivery methods for treating DR, and discussed their respective development potentials. Recently, novel receptor inhibitors and agonists, such as aldose reductase inhibitors, angiotensin-converting enzyme inhibitors, peroxisome proliferator-activated receptor alpha agonists, and novel drugs, have been reported as effective in delaying DR. Furthermore, with continuous advancements in nanotechnology, a new form of drug delivery has been developed that can address certain limitations of clinical drug therapy, such as low solubility and poor penetration. With an in-depth study of the pathogenesis of DR, many new promising therapeutic targets have emerged, and some progresses have been made in the processes of neuroprotection and regeneration. Here, we presented a comprehensive review of the current clinical therapies and delivery methods for patients with DR, and discussed the potential of new therapeutic targets. This review serves as theoretical basis for future studies on the treatment of DR..